Synthesis and Characterization of Na3V2(PO4)2F3 Based Cathode Material for Sodium Ion Batteries. (10th December 2015) - Väli, Ronald; Möller, Priit; Jänes, Alar
Abstract : Na3 V2 (PO4 )2 F3 was synthesized via two-step carbothermal reduction from NaF and VPO4 intermediate precursor and tested as cathode material for aqueous and non-aqueous Na-ion batteries. The synthesized material was characterized using XRD, SEM-EDX, TOF-SIMS. The cyclic voltammetry and charge/discharge measurements for non-aqueous system indicated that the intercalation / deintercalation of Na + ions is being carried out in two steps: the first one at 3.5/3.7 V and the second one at 4.1/4.3 V, indicative for a structural transformation of the cathode material. Discharge capacity of 55 mA g -1 was measured for the first cycle. However, the capacity decreased nearly 50 %, to 22 − 25 mA g -1 after the second galvanostatic cycle within 3.0 – 4.5 V. Discharge capacity decreases during the first 10 cycles but stabilizes after 50 cycles, maintaining ~ 20 mA g -1 after 3000 cycles. Cycling in aqueous media showed even faster capacity fade.